Histopathological Examination of Dyspeptic Patients With and Without Hiatal Hernia - Vural, Selahattin; Poyraz, Bekir; Dulger, Ahmet Cumhur (Eastern Journal of Medical Sciences, 2018)
Background: Hiatal hernia with dyspeptic complaints is a severe disease which disturbs the quality of life. Pathological findings in endoscopy are an important factor in the treatment of these patients. Objective: To investigate the histopathological differences related to hiatal hernia in dyspeptic patients. Material and Methods: A retrospective study was conducted of 116 patients with dyspeptic complaints. The patients were divided into two groups according to the presence of hiatal hernia. Biochemical tests and endoscopic biopsy results of these groups were compared. Results: The mean age of our study population was 52.4 years where, 50% were male and 50% were female. Hiatal hernia was found in 44.8% of the patients and 22.4% of the patients had intestinal metaplasia. The rate of intestinal metaplasia was found to be statistically lower in the hiatal hernia group (p=0.011). Conclusion: Intestinal metaplasia is less frequently found in patients with hiatal hernias in our study; it may be attributed to the fact that these patients had earlier dyspeptic complaints and therefore, earlier medical treatment and earlier initiation of a protective gastric diet.